2008
DOI: 10.1037/a0013098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retention in first grade on children's achievement trajectories over 4 years: A piecewise growth analysis using propensity score matching.

Abstract: The authors investigated the relatively short-term and longer term effects of grade retention in 1st grade on the growth of mathematics and reading achievement over 4 years. The authors initially identified a large multiethnic sample (n = 784) of children who were below the median in literacy at school entrance. From this sample, the authors closely matched 1 retained with 1 promoted child (n = 97 pairs) on the basis of propensity scores constructed from 72 background variables and compared growth of retained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 70 publications
9
76
0
1
Order By: Relevance
“…Further, it is possible that, because more half-day children are retained and have an extra year of schooling before taking the CST, our estimates of the effects of full-day kindergarten on second-grade academic achievement are lower than they truly should be. However, recent literature on early grade retention suggests that being retained in kindergarten or first grade is associated with negative or neutral academic outcomes (Burkam et al, 2007;Hong & Raudenbush, 2005;Wu, West, & Hughes, 2008). We also tested the effect of full-day kindergarten on CST scores for only students who were not retained, and the results are quite similar to the results including retained students (results available from authors).…”
supporting
confidence: 56%
“…Further, it is possible that, because more half-day children are retained and have an extra year of schooling before taking the CST, our estimates of the effects of full-day kindergarten on second-grade academic achievement are lower than they truly should be. However, recent literature on early grade retention suggests that being retained in kindergarten or first grade is associated with negative or neutral academic outcomes (Burkam et al, 2007;Hong & Raudenbush, 2005;Wu, West, & Hughes, 2008). We also tested the effect of full-day kindergarten on CST scores for only students who were not retained, and the results are quite similar to the results including retained students (results available from authors).…”
supporting
confidence: 56%
“…Similarly, Pierson and Connell (1992) reported for a same-grade comparison study that effects of grade retention persisted only in the short-term but diminished within 2 or more years after the repeated year. Wu, West, and Hughes (2008a) found with both same-age and same-grade comparisons that grade-standardized scores obtained from mathematics and reading were higher for retained students than for promoted students in the short-term (about half a year after retention). However, this advantage disappeared in the long-term (2.5 years after retention).…”
Section: Short-term and Medium-term Effects Of Grade Retention On Acamentioning
confidence: 88%
“…Often, when a student fails to meet grade-level performance criteria, retention is considered because the educator believes that an additional year in the curriculum will help the student mature and prepare for the demands of the next grade level (Wu et al 2008). To the contrary, decades of research have demonstrated that retention does not benefit the student educationally, and may even have deleterious consequences for achievement and the student's social and emotional wellbeing.…”
Section: Possible Deleterious Effects Of Grade-level Retentionmentioning
confidence: 98%